Measured GFR by Utilizing Population Pharmacokinetic Methods to Determine Iohexol Clearance - Åsberg, Anders (Kidney Int Rep, 2019)
INTRODUCTION: There is an increasing demand for accurately measured glomerular filtration rate (GFR). Iohexol serum clearance has become a new gold standard, but it is challenging when GFR is low and 24-hour sampling is required for accurate results. The primary aim of this study was to develop an iohexol pharmacokinetic population model for accurate determination of individual GFR using limited sampling for up to 5 hours also when renal function is <40 ml/min. METHODS: A nonparametric iohexol population pharmacokinetic model was developed with rich data from 176 patients. In a validation cohort of 43 patients, a model-determined GFR (iohexol clearance) using different limited sampling strategies for up to 5 hours was compared with the strategy currently used in routine care, a log-linear 2-point method. In all, 1526 iohexol concentrations were used, from patients ranging in age from 1 to 82 years and GFR from 14 to 149 ml/min. RESULTS: The clinical 2-point method showed insufficient agreement compared with reference values; 15% of GFR values had an error of greater than ±10% even when sampling for 24 hours when estimating GFR <40 ml/min per 1.73 m(2) (standard procedure). Restricted sampling the first 5 hours with the population model required 4 samples to determine GFR accurately. This strategy showed excellent agreement with the reference; <3% of GFR values had an error greater than ±10 %. CONCLUSION: Using an iohexol population pharmacokinetic model allows for accurate determination of GFR within 5 hours when applying 4 optimally timed samples, even in patients with GFR <40 ml/min.